Hereditary haemorrhagic telangiectasia manifesting as subdural empyema. (3rd May 2016) - Solanki, Sandeep P.; Taylor, Christopher; Robertson, Iain
Abstract: Hereditary haemorrhagic telangiectasia (HHT) also known as Osler-Weber-Rendu disease is a rare autosomal dominant condition causing vascular dysplasia. Cerebral abscess formation, secondary to paradoxical septic emboli via HHT-derived pulmonary arteriovenous malformations (pAVMs) in this context is well documented. Herein, we present the first case of subdural empyema with this aetiology.